Implementasi Metode Pembelajaran Problem Solving Pada Pembelajaran Tematik Di Kelas IV SD Negeri 3 Pasarmadang Kecamatan Kota Agung Kabupaten Tanggamus - Hulan Hulan; Qomario Qomario; Putry Agung (Gayaku Publisher, 2022)
Problem-solving is a very effective method when applied in the learning process. Thematic learning is integrated learning that links several subjects divided into several themes and sub-themes to direct students to be more active, and creative in developing their thinking. This type of research is descriptive qualitative research. This research was conducted at elementary school 3 Pasarmadang in grade IV. The subjects of this study were the principal, the thematic teacher/class teacher, and the fourth-grade students with a total of 28 students. Data collection techniques used are observation, interviews, and documentation. The data that has been obtained during the study were analyzed by reducing the data, presenting the data, drawing conclusions, and triangulation from the results of the study. Based on the results of research and analysis on the implementation of problem-solving learning methods in thematic learning in class IV at elementary school 3 Pasarmadang, it can be concluded that the teacher makes a lesson plan (RPP) first. In the RPP there are 3 activities, namely initial activities, core activities, and closing activities. In the core activity, the teacher provides material using 6 stages of problem-solving methods, namely the problem identification stage, the representation/presentation stage of the problem, the solution planning stage, the implementing/implementing planning stage, the planning assessment stage, and the evaluation stage of the solution. At the end of the learning process, the teacher evaluates the material. From the results obtained by the researchers, the problem-solving implementation method has been able to be applied well in the fourth grade at elementary school 3 Pasarmadang.